Distributed Localization in Cluttered Underwater Environments - Hussain, M; Trigoni, N (2010)
Mapping and exploration of closed fluid tanks, such as nuclear waste storage tanks and water sewage treatment ponds, by a swarm of underwater robots requires them to be aware of their positions, as they traverse the depths of the tank. This paper considers the challenges faced in localizing robots using reference-based localization in such clutter-prone environments. Clutter affects localization in two ways: it blocks reference communication signals, effectively preventing them from reaching the more remote regions in the tanks, and, second, it leads to the formation of non-line-of-sight (NLOS) distance measurements. In this paper, we consider the application of distributed localization techniques to cluttered environments and assess their performance. We also investigate how to place robots in a multi-hop network to improve the accuracy of position estimation in the far-fetched regions of the tank, when distributed localization is used.